International governance of war-torn territories rule and reconstruction - Caplan, Richard (Richard D.); Oxford eBooks (New York ; Oxford : Oxford University Press, 2005)
Drawing on extensive interviews with international officials independent analysts, and journalists, as well as many official documents, Richard Caplan examines the nature of international administration operations since the mid-1990s, their effectiveness, and the key operational and political challenges which arise.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Peacekeeping forces; Peace-building.; Conflict management; Electronic books